Career verdure and wellness signification among academic expatriate members of Malaysian private university - Irma Wani Othman; Muhammad Safuan Yusoff; Mohd Kamal Mohd Shah; Mohd Sohaimi Esa; Romzi Ationg; Anna Lynn Abu Bakar (Artesis Hogeschool Antwerpen - Hoger Instituut voor Vertalers en Tolken, 2021)
The influx of professionals from abroad through the diaspora of career exploration shows a significant increase. Rationally, expatriate individuals who decided to expat must intend to utilise the development of their career development in the host country. In line with the era of globalisation and internationalisation policy of higher education, the understanding of the significance of the career verdure and wellness of expatriates is a critical element in the career development of international staff. The two main objectives of this study are (i) to identify the significance of career verdure and wellness among expatriate academics members of Private Universities of Malaysia and (ii) to work on an assessment that shows the tendency of expatriates in making choices to work in Private Universities of Malaysia. Based on the determination made from the purposeful sampling, a total of 35 expatriate academicians from three private universities willingly gave their consent to participate as study informants. Using a qualitative approach through in-depth interview methods, this study identifies the relevance of expatriate academician’s attendance who choose to serve in Private Universities of Malaysia and the significance of verdure and wellness in expatriate career achievement as an academician. The results of the research include four (4) key findings namely (i) Generating Income Maximization, (ii) Conducive Workplace Environment, (iii) Stimulus of Targeted Job Movement and (iv) Harmony of the Host Country. The findings clearly show that these expatriate academicians have used career paths through expatriation done to develop their careers, further achieving a level of success in a much better direction than what they gained while in their home country. Meanwhile the tendency of the decision to migrate among the expatriates is also seen as a relevant initiative on the part of the university management in order to optimally realize efforts to recruit, select and retain international staff, especially in Private Universities of Malaysia.